Betraying Identities in Mourning with an Ethic of Discomfort. (February 2017) - Beaumont, Thomas E.
Contemporary practices of grieving those lost to war violence are largely framed by epistemological assumptions that often essentialize the identities of both the dead and those mourning. In addressing the desirability of these identity categories through a critical examination of contemporary practices, I draw on Foucault's ethic of discomfort to foreground the contingent and the singular that are often obfuscated by practices of mourning and memorialization. If, instead of conflating selfhood and grieving, identities in mourning can be viewed in their contingency as the decision to grieve in certain ways, practices of mourning can facilitate an undoing of the identity politics in play. Ultimately, I argue, we must risk ourselves in ways that surpass the utility of the contemporary identity politics surrounding mourning by refusing the current practices that define expectations regarding intelligible forms of grieving those lost to war violence. It is in the risk of betraying our loved ones in those solidified identities that allow us to rethink the requirements for moral responsibility in ways that undo, rather than solidify, identity categories within practices of grieving. In doing so, we can begin to explore potential for ridding ourselves of claims that stratify and separate communities through an identity politics and claims that justify the use of violence and domination in the preservation of those identities.